Intracellular Regulation of Cross-Presentation during Dendritic Cell Maturation - Wagner, Claudia S. (Public Library of Science, 2013)
We have investigated the effect of different maturation stimuli on the ability of mature dendritic cells (DCs) to cross-present newly acquired particulate antigens. Cross-presentation was impaired in DCs matured by treatment with TNF-α, CpG and LPS, but was less affected upon CD40L-induced maturation. The difference could not be explained by decreased antigen uptake or translocation into the cytosol, but decreased cross-presentation ability did correlate with increased phagosomal/lysosomal acidification. Nevertheless, intra-phagosomal degradation of OVA was not increased in matured samples, suggesting that decreasing phagosomal pH may also regulate cross-presentation by a mechanism other than enhancing degradation.